Water level in the Riviera catchment (Cocody, Abidjan, Côte d'Ivoire) (2020-) - Seguis, Luc; Perrin, Jean-Louis; Koffi, Ehouman Serge; Dutremble, Clement; Dao, Amidou; Zahiri, Eric-Pascal (DataSuds, 2022)
The Riviera watershed (Abidjan, Côte d'Ivoire) is urbanized and prone to flooding from overflowing stormwater drainage channels. This dataset provides instantaneous water level (cm) measured every minute in Palmeraie station in Cocody, Abidjan (Longitude -3,953755 Latitude 5,374638) since June 2020. Each water level station is equipped with a piezometric probe associated to a HYDREKA standalone data recorder with a communication capability (Octopus LX). A manually read staff gauge is used to control the water level determined by the pressure probe. Data are collected monthly.